Influence of the duration of led lighting on the state of the pigment fund of plas-tids of vegetable pea microgreen - Pashkevich, Hanna M.; Tchaikovsky, Andrey I.; Rupasova, Zhanna A.; Zadalia, Viktoriya S. (Journal of the Belarusian State University. Ecology, 2022)
The article presents the results of a study of the duration of LED lighting (8, 10, 12, 14, 16 hours) when growing vegetable pea microgreens under light culture conditions in a phytotron equipped with an irradiating rack-type plant FLORA LED 300/2/4 with ten LED lamps DSP08-3x12- 004 UHL4, for the content of photosynthetic pigments (chlorophylls a and b, B-carotene and xanthophylls) in the samples of manufactured products. It was found that the most pronounced activation of the accumulation of both green and yellow plastid pigments in vegetable pea microgreens - by 12-19 % and 33 %, respectively, compared with the control (12-hour exposure), was established at 14- and 16-hour illumination, which contributed to an increase in the content of B-carotene by 51 and 33 %, while 8-hour illumination caused the activation of the accumulation of the latter by only 12 % in the absence of a significant effect on the rate of its biosynthesis of 10-hour illumination. At 14- and 16-hour exposure, the most significant enrichment of pea microgreens with xanthophylls was found in the experiment by 27 and 33 % compared with the control. In accordance with the decrease in the content of plastid pigments in pea microgreens, the following sequence of experiment variants with different illumination durations is indicated: 14 hours > 16 hours > 8 hours > 12 hours > 10 hours. It was found that the most saturated stock of photosynthetic pigments in the experiment was characterized by microgreen samples at 16 and especially at 14-hour duration of LED lighting, while the most depleted - at 8- and especially at 10-hour duration.